(untitled) - Toita, Yasuji (New York, 1970)
An authoritative guide... The book explains everything lucidly and painstakingly--the background, the facts, the emotions. This book shows us the theatre from the inside, with deep understanding of its meaning and purpose.
Keywords: Kabuki,Kabuki plays; History and criticism